3D Printed multilayer overlapping resonators for low-frequency broadband sound absorption: mechanism analysis and corresponding modified theoretical method - Yiming Zhao; Zichao Guo; Jie Ye; Junjie Deng; Xinying Lu; Kexin Zeng; Zhonggang Wang; Zhendong Li (Virtual and Physical Prototyping)
Broadband low-frequency sound absorption is highly sought in engineering applications, but the size of sound-absorbing metamaterials still poses challenges. By revisiting the Helmholtz resonator, we propose a multi-layer overlapping structure. This structure adopts a simple design of nested multiple Helmholtz resonators, creating a composite effect of coupling a three-dimensional buckling acoustic cavity with discontinuous cross-sectional effects, significantly improving the effective depth of the external cavity within a finite dimension. To reveal its complex characteristics, a high-fidelity correction method was proposed to calculate the increase in the effective depth of the cavity structure. Experimental validation has been conducted to evaluate the accuracy of the current model. This structure significantly increases the effective depth by about 38% with a total thickness of 63 mm, achieving broadband absorption from 320 to 690 Hz using non-parallel units. This work provides new and unique insights for designing acoustic metamaterials.